Pemberdayaan Kelompok Ibu-ibu Aisyiyah dalam Diversifikasi Produk Olahan Nira Mendukung Ketahanan Pangan dan Ekonomi Keluarga - Bustang Bustang; Anti Landu Landu; Andi Iswan Iswan; Masitah Masitah; Asni Asni (Universitas Muhammadiyah Sidenreng Rappang, 2025)
Abstract. Community service activities were carried out in Tikonu Village, Wundulako Subdistrict, Kolaka Regency, with the target partner being the Aisyiyah women's group. The partnership program aimed to empower the Aisyiyah women's group to be able to process palm sap into value-added products such as palm sugar, natade coco, and palm vinegar with hygienic standards. The approach used was participatory and appropriate technology transfer, involving universities as facilitators and community partners as the main implementers. The main activities included: Technical training on processing palm sap into various healthy and durable processed products; Introduction of simple technologies such as bottle sterilization and hygienic filtration equipment; Business management assistance, including financial record keeping, packaging, and product labeling; Digital marketing training using social media and online platforms to expand market reach; and Monitoring and evaluation of business sustainability through the formation of group action teams. The results of these activities show a significant improvement in the technical and managerial skills of 70% of the partners. The social impact that has emerged is an increase in women's participation in village economic activities, increased social solidarity within the group, and a growing awareness of the importance of productive and sustainable use of local resources. Abstrak. Kegiatan pengabdian kepada masyarakat dilaksanakan di Desa Tikonu, Kecamatan Wundulako, Kabupaten Kolaka, dengan mitra sasaran kelompok ibu-ibu Aisyiyah. Program kemitraan bertujuan untuk memberdayakan kelompok ibu-ibu Aisyiyah agar mampu mengolah nira menjadi produk bernilai tambah seperti gula semut, natade coco, dan cuka nira dengan standar higienis. Pendekatan yang digunakan adalah partisipatif dan transfer teknologi tepat guna, dengan melibatkan perguruan tinggi sebagai fasilitator dan mitra masyarakat sebagai pelaksana utama. Kegiatan utama meliputi: Pelatihan teknis pengolahan nira menjadi berbagai produk olahan sehat dan tahan lama; Pengenalan teknologi sederhana seperti alat steril botol dan penyaringan higienis; Pendampingan manajemen usaha, termasuk pencatatan keuangan, pengemasan, dan pemberian label produk; Pelatihan pemasaran digital menggunakan media sosial dan platform daring untuk memperluas jangkauan pasar; serta Monitoring dan evaluasi keberlanjutan usaha melalui pembentukan tim penggerak kelompok. Hasil kegiatan menunjukkan peningkatan signifikan pada keterampilan teknis dan manajerial mitra 70%. Dampak sosial yang muncul meningkatnya partisipasi perempuan dalam kegiatan ekonomi desa, meningkatnya solidaritas sosial kelompok, serta tumbuhnya kesadaran terhadap pentingnya pemanfaatan sumber daya lokal secara produktif dan berkelanjutan.